The spatial structure of nature use conflicts in the Kostanay region (Journal of Geography and Environmental Management, 2024)
In scientific research, modern conflicts of natural resource use have been identified in the territory of the Kostanay region, and their mapping has been conducted. Landsat 9 satellite images and the results of field research conducted in 2023 were used as the initial data for mapping the structure of conflicts of natural resource use. As a result of the research, the spatial structure of conflicts of natural resource use in the studied area was determined, and the degree of their expression was defined. Based on the analysis of the spatial-territorial structure of natural resource use, the authors have developed a map of natural resource use and a map of conflicts of natural resource use for the studied region. The authors identified and analyzed that the most pronounced conflicts of natural resource use have arisen between the following types of conflicts: settlement-nature conservation; settlement-transport-industrial; recreational-transport; nature conservation-transport-industrial; water management-transport-industrial; and forestry-transport. During the research, it was determined that the collision of interests in antagonistic relationships not only complicates the state of the natural environment of the studied region but also contributes to the destruction and gradual degradation of components of the natural environment, forming strongly expressed multifunctional conflicts of natural resource use. The results of the conducted research can be applied to optimize the territorial-spatial structure of natural resource use and to organize environmental monitoring in the Kostanay region.
Keywords: type of nature management, conflict of nature management, antagonistic functions, the spatial structure of nature management, the Kostanay region.